Identifikasi Timbulan Sampah Domestik Pada Kawasan Permukiman Pesisir Di Desa Pangkalan Buton - Asmadi, Asmadi; Akbar, Aji Ali; Sudrajat, Jajat; Gusmayanti, Evi; Adhitiyawarman, Adhitiyawarman (Jurnal Teknologi Lingkungan Lahan Basah, 2025)
Waste management in Pangkalan Buton Village is a crucial issue in sustainable development, especially in vulnerable coastal areas. This research examines the current condition of waste management facilities, the level of compliance with environmental regulations, and public participation. Findings show that daily waste generation reaches 0.4 kg per person, mostly consisting of biodegradable organic waste. However, the lack of recycling and composting infrastructure hinders proper processing. Waste collection services are inconsistent, and public awareness remains low. The study recommends enhancing community education through continuous outreach programs and strengthening the role of the DPRKPLH. Developing modern waste management infrastructure, implementing data-based monitoring and evaluation systems, and enforcing environmental laws are also essential. Collaboration between local government, private sectors, and communities should be improved, especially through CSR initiatives and the use of digital tools like reporting apps. Effective waste management not only preserves the environment but also creates economic opportunities through recycling and compost production. Ultimately, a holistic and integrated approach involving education, infrastructure, law enforcement, and technological innovation is necessary to achieve efficient, sustainable, and community-supported waste management in Pangkalan Buton Village.